The Effect of Export, Import, and Exchange Rate on Economic Growth in Four ASEAN Countries (Singapore, Thailand, Malaysia, Philippines) in The Period 2017-2024 - Anggraini, Pramuditya; Setyowati, Eni (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of exports, imports, and exchange rates on economic growth in four ASEAN countries Singapore, Thailand, Malaysia, and the Philippines during the 2017-2024 period. The data used are secondary data obtained from official publications such as the Central Statistics Agency (BPS) and other scientific sources. The analytical method applied is panel data analysis using Eviews 10 software. The models employed include the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with model selection tests conducted using the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results show that the most appropriate model is the Fixed Effect Model (FEM). Based on the partial test (t-test), the import and exchange rate variables have a significant effect on economic growth, while the export variable shows no significant influence. The Adjusted R² value of 0.437 indicates that 43.7% of the variation in economic growth is explained by the three independent variables, while the remaining 56.3% is explained by other factors outside the model. These findings suggest that exchange rate stability and the management of import activities play an important role in promoting economic growth in the ASEAN region.